The Role of Keuchik in Activity of City without Slum (Kotaku) in Gampong Lampulo Kuta Alam Regency Banda Aceh - Ismail; Salahuddin; Fuady (Britain International for Academic Research (BIAR) Publisher, 2020)
Keuchik is the Head of Government at Gampong (village) level, which is tasked with holding village government, carrying out development, and being involved in village cleaning activities through mutual assistance activities to carry out slum-free settlement activities to give birth to clean communities. Therefore, Keuchik Gampong (Village Head) in planning involves community members. The City without Slums Program (KOtaku) is a strategic effort of the government in dealing with slums especially in Banda Aceh. In this case, Keuchik's effort in making planning is basically a deliberate, directed, coordinated and integrated process with the aim of improving the welfare of the community so that they are responsible for the plans that have been made. The purpose of this study is to analyze the role of Keuchik Gampong (Village Head) in implementing the City without Slum (KOtaku) program in Lampulo Village, Kuta Alam District, Banda Aceh City and examine various obstacles when Keuchik (Village Head) performs its role in implementing the City Without Slum (KOtaku) program. This study uses qualitative methods to describe the social reality of KOtaku. To obtain representative data, the researchers used data collection techniques through observation, interviews and documentation studies. Next analyze the data, reduce the data, conclude or verify. Checking the validity of the researchers' data is done by way of participation and extension of observations. The results showed that the existence of keuchik can give birth to a city free from slums because it can maintain good hygiene. This is part of the success of the development achieved because Keuchik Gampong (Village Head) also carries out supervision in every activity, so that it can provide various alternatives to various problems that arise. While the obstacles for Keuchik Gampong (Village Head) are in carrying out their role, many community members cannot be physically involved in KOtaku activities due to the density of other activities that are difficult to leave. However, with the role of Keuchik Gampong (Village Head), the community who could not physically attend made other contributions in the form of the budget needed in my KOtaku activities.